Contribution of nonprimate animal models in understanding the etiology of schizophrenia - Lazar, Noah L. (Canadian Medical Association, 2011)
Schizophrenia is a severe psychiatric disorder that is characterized by positive and negative symptoms and cognitive impairments. The etiology of the disorder is complex, and it is thought to follow a multifactorial threshold model of inheritance with genetic and neurodevelopmental contributions to risk. Human studies are particularly useful in capturing the richness of the phenotype, but they are often limited to the use of correlational approaches. By assessing behavioural abnormalities in both humans and rodents, nonprimate animal models of schizophrenia provide unique insight into the etiology and mechanisms of the disorder. This review discusses the phenomenology and etiology of schizophrenia and the contribution of current nonprimate animal models with an emphasis on how research with models of neurotransmitter dysregulation, environmental risk factors, neurodevelopmental disruption and genetic risk factors can complement the literature on schizophrenia in humans.